PENGARUH BUDAYA ORGANISASI TERHADAP ORGANIZATIONAL CITIZENSHIP BEHAVIOR (OCB) DOSEN DI UNIVERSITAS KRISTEN INDONESIA (UKI) - Bernadetha Nadeak (Pascasarjana Universitas Kristen Indonesia Program Magister Administrasi/Manajemen Pendidikan, 2016)
ABSTRACT This research ivestigates the effect of organizational culture on the lecturers’ organizational citizenship behaviour at Christian University of Indonesia. The research is aimed to know whether there is an effect of organizational culture on the lecturers’ organizational citizenship behaviour or not. The method of the research used is quantitative method with a survey design. There are 314 lecturers were chosen to be the population of this researh and from the population 109 lecturers were chosen to be the sample of this research. The data of the research was collecting through a set of questionnaire. The questionnaire was given to the all of the chosen sample. After the data was collected so it was analyzed, and after that a finding was drawn. The finding is; there is an effect of organizational culture on the lecturers’ organizational citizenship behaviour at Christian University of Indonesia. By then, in order to improve the the lecturers’ organizational citizenship behaviour, so organizational culture is an important element needs considering by the higher institution whether it is public higher institution or private higher institution. Keywords: organizational culture, organizational citizenship behavior. ABSTRAK Penelitian ini membahas tentang pengaruh budaya organisasi terhadap organizational citizenship behaviour dosen di Universitas Kristen Indonesia. Adapun tujuan dari penelitian ini adalah untuk mengetahui apakah ada pengaruh budaya organisasi terhadap organizationl citizenship behaviour dosen. Metode penelitian yang digunakan pada penelitian ini adalah metode penelitian kuantitatif dengan pendekatan survey. Adapun populasi dan sampel penelitian ini adalah berjumlah 314 orang dosen, dan terdiri dari 109 orang. Adapun teknik pengumpulan data yang digunakan dalam penelitian ini adalah instrumen kuesioner. Peneliti memberikan kuesioner kepada seluruh sampel terpilih. Setelah data dianalisis maka ditemukanlah kesimpulan dari penelitian ini yaitu terdapat pengaruh budaya organisasi terhadap organizationl citizenship behaviour dosen di Universitas Kristen Indonesia. Dengan demikian, dalam rangka perbaikan organizationl citizenship behaviour dosen maka budaya organisasi menjadi elemen yang penting diperhatikan oleh lembaga-lembaga perguruan tinggi baik negeri maupun swasta. Kata kunci: pengaruh, budaya orgasisasi, organizational citizenship behaviour.